The Role of the Administrative Service System Integrated Bureaucracy (SADASBOR) in Realizing Good Governance in Tasikmalaya Regency - Ade Setiadi; Mulyaningsih; Ikeu Kania (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The use of digital technology in public administration is an important strategy in improving the quality of governance. Tasikmalaya Regency has implemented the Integrated Bureaucratic Administration Service System (SADASBOR) as a solution to speed up the administrative process and increase transparency and accountability in the bureaucracy. This system is designed to support the implementation of good governance by ensuring efficiency, effectiveness, and openness in administrative services. However, in its implementation, there are still a number of challenges, such as the resistance of the State Civil Apparatus (ASN) to digitalization, limited technological infrastructure, and the risk of data leakage. This study aims to examine the role of SADASBOR in realizing good governance in Tasikmalaya Regency and identify the obstacles faced in its implementation. This study uses a qualitative approach with a descriptive case study method. Data was collected through in-depth interviews with ASN, direct observation of the implementation of the system, and studies related to policies and regulations governing the implementation of SADASBOR. Furthermore, the stages of data reduction, data presentation, and conclusion drawn, guided by the principles of good governance. The results of the study reveal that SADASBOR has played a role in improving administrative efficiency, transparency, and bureaucratic accountability. However, there are several obstacles that still need to be overcome, such as the lack of readiness of ASN in adapting to the digital system, limited server capacity. Therefore, strategic steps are needed, such as strengthening technological infrastructure, increasing digital literacy for civil servants.